Arq in ars. La arquitectura en el arte medieval - Corrales Fernández, Tamara (2015)
Although the architecture and art have had a close relationship as builders of human culture over the years, both have developed in the technical and creative field. The relationships that exist between the two disciplines can be contrasted or interpolated from the appearance of one into the other. In this case, we will see how the architecture appears in the art, that in developing of the pictorial and compositional technique, gives greater showcase the emergence of architecture as one of the protagonists of the message you want to express, determining times, styles and even specific situations.